Hubungan Interaksi Sosial dengan Kualitas Hidup Lansia di Wilayah RW 01 Pejaten Barat Jakarta Selatan - Fadhillah Sukmawaty; Andi Mayasari Usman; Susanti Widiastuti (Universitas Malahayati Lampung, 2023)
ABSTRACT According to Databoks there is an increase in the Life Expectancy Rate (AHH) of the Indonesian population at birth for 73.5 years in 2021, this figure has increased by 0.1 point from the previous year which was 73.4 years. Data from the Director General of Population and Civil Registration (Dukcapil) shows 30.16 million elderly people in Indonesia in 2021. The elderly population is those aged 60 years and over. The portion of this group reaches 22.01% of the total population in Indonesia, which amounts to 273.88 million people. More precisely, there are 11.3 million people (37.48%) of the elderly population aged 60-64 years. Then there are 7.77 million people (25.77%) aged 65-69 years. After that there were 5.1 million people (16.94%) aged 70-74 years, and 5.98% (19.81%) aged over 75 years (Databoks, 2022). as many as 942.8 thousand elderly people are in the capital city in 2020. This number is projected to increase to 998.39 thousand people in 2021 and 1.05 million in 2022. In 2023 the elderly will again increase to 1.1 million people and in in 2024 there will be 1.17 million people. Based on a preliminary study conducted by 7 elderly researchers in Rt. 12 West Pejaten prefer to shut themselves up at home, rarely mingle with the environment, never seen when there are social events in the environment such as community service, this is because they close that the elderly are no longer able to help with environmental social activities, because the body functions of the elderly are already is not optimal in people who are younger than him. This study aims to determine the relationship between social interaction and the quality of life of the elderly in RW 11 Pejaten Barat. The design of this study used a quantitative method with a cross sectional approach. The population in this study were 50 elderly people in RW 01 Pejaten Barat. The sample in this study were 50 elderly people in RW 01 Pejaten Barat. The sampling technique used in this study uses the total sampling technique. The instruments used were the WHOQOL questionnaire and the social interaction questionnaire. Based on the results of the Chi Square Statistical Test on Social Interaction with Quality of Life in the Physical Domain, a significant value of p value was 0.036, p a or significant 0.036 0.05, so there is a relationship between Social Interaction and Quality of Life in the Elderly in RW 01. West Pejaten. Social interactions carried out by the elderly in the RW 11 Pejaten Barat area can affect the Quality of Life of the Elderly so that the quality of life for the elderly becomes better. Keywords : Social Interaction, Quality of Life, Elderly. ABSTRAK Menurut Databoks ada peningkatan Angka Harapan Hidup (AHH) penduduk Indonesia pada saat lahir selama 73,5 tahun pada 2021, angka tersebut naik 0,1 poin dari tahun sebelumnya yang selama 73,4 tahun. Data pada Direktoral Jenderal Kependudukan Dan Pencatatan Sipil (Dukcapil) menunjukan 30,16 juta jiwa penduduk lanjut usia (lansia) di Indonesia pada 2021. Penduduk lansia adalah mereka yang berusia 60 tahun ke atas. Kelompok ini porsinta mencapai 22,01% dari total penduduk di Indonesia yang berjumlah 273,88 juta jiwa. Rincian lebih tepatnya sebanyak 11,3 juta jiwa (37,48%) penduduk lansia berusia 60-64 tahun. Kemudian ada 7,77 juta jiwa (25,77%) yang berusia 65-69 tahun. Setelahnya ada 5,1 juta penduduk (16,94%) berusia 70-74 tahun, serta 5,98% (19,81%) berusia diatas 75 tahun (Databoks, 2022). Sebanyak 942,8 ribu lansia berada pada ibu kota pada tahun 2020. Jumlah tersebut diproyeksikan naik menjadi 998,39 ribu jiwa pada tahun 2021 dan 1,05 juta pada tahun 2022. Pada tahun 2023 lansia kembali bertambah menjadi 1,1 juta jiwa dan pada tahun 2024 akan berjumlah 1,17 juta jiwa. Berdasarkan studi pendahuluan yang dilakukan peneliti 7 lansia di Rt. 12 Pejaten barat lebih senang mengurung diri di rumah, jarang berbaur dengan lingkungan, tidak pernah tampak saat ada acara social di lingkungan seperti kerja bakti, hal ini disebabkan karena mereka beranggapan bahwa lansia sudah tidak dapat membantu kegiatan social lingkungan, karena fungsi tubuh lansia yang sudah tidak maksimal dair pada orang yang lebih muda darinya. Penelitian ini bertujuan untuk mengetahui Hubungan Interaksi Sosial Dengan Kualitas Hidup Lansia Di Wilayah RW 11 Pejaten Barat. Desain penelitian ini menggunakan metode kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah 50 lansia di wilayah RW 01 Pejaten Barat. Sampel dalam penelitian ini adalah 50 lansia di wilayah RW 01 pejaten Barat. Teknik sampling yang digunakan dalam oenelitian ini menggunakan teknik total sampling. Instrument yang digunakan adalag kuisoner WHOQOL dan kuisoner interaksi social. Berdasarkan hasil Uji Statistik Chi Square pada Interaksi Sosial Dengan Kualitas Hidup Domain Fisik diperoleh nilai signifikan p value 0,036, diperoleh p a atau signifikan 0,036 0,05 maka ada hubungan antara Interaksi Sosial dengan Kualitas Hidup Pada Lansia Di Wilayah RW 01 Pejaten Barat. Interaksi social yang dilakukan oleh lansia di wilayah RW 11 Pejaten Barat dapat mempengaruhi Kualitas Hidup Lansia sehingga kualitas hidup lansia menjadi lebih baik Kata kunci : Interaksi Sosial, Kualitas Hidup, Lansia